ESTIMASI NILAI EKONOMI KAWASAN WISATA RELIGIUS MAKAM KAWAH TENGKUREP DENGAN PENDEKATAN TCM DAN CVM - Erdah Litriani (Jurnal Bina Bangsa Ekonomika, 2021)
The problems that occur are not only too close to the container port and not well organized, the Tengkurep crater grave area is also a number of other problems. As less conducive in terms of security. Another problem is the lack of information in various media regarding the area, which causes very few tourists who come every month, except in certain months, such as before the month of Ramadan and the Prophet's birthday. Willingness to pay or willingness to pay from visitors is influenced by several factors, namely: income, age, education level, gender, and religiosity level. Willingness to Accept or willingness to accept the impact of the population is influenced by several factors, namely: income, distance, age, level of education, and level of religiosity. The factors that influence the number of visits are income, travel costs, age, education level, gender, and level of religiosity. The estimated economic value of the Kawh Tengkurep grave area is based on the Travel Csot Method approach or travel costs of Rp. 79,300,000. Estimation of the economic value of the tengkurep crater grave area using the CVM (Contingent Valuation Method) approach using Willingness to pay or willingness to pay from visitors of Rp. 75. 937,500 The estimated economic value of the Tengkurep crater tourism area using the CVM (contingent valuation method) approach using the Willingness to Accept (WTA) or the community's willingness to accept the positive and negative impacts of the existence of the tengkurep crater grave area of ​​Rp. 202,497,828,571